Écrire avec Flaubert - Anne Herschberg Pierrot (Flaubert: Revue Critique et Génétique)
I am interested in the way in which many writers of the 20th and 21st centuries, from Kafka to Claude Simon, Roland Barthes, Pierre Michon, or Jean-Philippe Toussaint, have demonstrated in their writings, their correspondence, or their interviews, an interest in Flaubert’s manner of writing, based on their reading of Flaubert’s correspondence, or on direct or indirect knowledge of Flaubert’s manuscripts. In the context of the myth that Flaubert represents for contemporary writing, the aim is to examine not so much the reception of the published work, but rather the imaginary relationship that these writers have with Flaubertian genesis, or Flaubertian discourse on the genesis of the work. Whether they express their affiliation or their refusal, they write with Flaubert. The article will compare three moments in time: the 1910s, around Kafka and Proust, the 1970s, around La Préparation du roman by Roland Barthes, the 2000s with Marie-Hélène Lafon.